Dinamika Motivasi Belajar Mahasiswa yang Sudah Menikah di IAIN Kerinci - Ahmad Khairul Nuzuli; Agung Tri Prasetia; Puji Kurnia; Rezki Rosalia Indah; Ria Julita Sari; Rahmat Rhafizt P (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2023)
Abstract: Students who decide to get married face various challenges in completing their studies. Learning motivation is a motivating factor for married students in carrying out their education process well. This study uses a qualitative method with a phenomenological approach. The research subjects were three married students from the Kerinci State Islamic Institute (IAIN). Data collection is done by interview. The results showed that the learning motivation of married students came from external sources, namely wanting to finish college so that after graduation, they could focus on taking care of their children and the support of parents and husbands to complete their studies immediately. The challenges in managing their learning motivation are related to the distance between home and campus—difficulty handling time in carrying out duties as a student and wife. The study's results also show that the ability to divide roles between husband and wife can help married students deal with time management problems. Keywords: Dynamics, Learning Motivation, Married, Students Abstract: Mahasiswa yang memutuskan menikah menghadapi berbagai tantangan dalam menyelesaikan studinya. Motivasi belajar menjadi faktor pendorong bagi mahasiswa yang sudah menikah dalam menjalani proses pendidikannya dengan baik. Penelitian ini menggunakan metode kualitatif dengan pendekatan Femenologi. Subyek penelitian mreupakan tiga mahasiswa Institut Agama Islam Negeri (IAIN) Kerinci yang sudah menikah . Pengumpulan data dilakukan dengan wawancara. Hasil penelitian menunjukkan bahwa motivasi belajar mahasiswa yang sudah menikah bersumber dari eksternal, yaitu ingin menyelesaikan kuliah agar setelah tamat bisa fokus mengurus anak dan adanya dukungan orang tua dan suami untuk segera menyelesaikan perkuliahannya. Tantangan yang dihadapi dalam mengelola motivasi belajarnya terkait dengan kendala jarak antara rumah dan kampus. Kesulitan memanajemen waktu dalam pelaksanaan tugas sebagai mahasiswa dan istri. Hasil studi juga menunjukkan bahwa kemampuan membagi peran antara suami dan istri dapt membantu mahasiswa yang sudah menikah dalam mengahadapi masalah manajemen waktunya. Kata kunci : Dinamika, Mahasiswa, Menikah, Motivasi Belajar